Diagnostic evaluation of the breast lump - Perrier, José Pedro; Cluzet, Oscar; Chevalier, Nelma; Cordero, Miguel; Müller, Augusto; Risi, Leonardo; Delgado, Bolívar (Cirugía del Uruguay, 1990)
The aim of this paper is to determine the nature of mammary nodules with the greatest efficiency.